EVALUASI PROGRAM TERAPI KOGNITIF PADA ANAK BERHADAPAN HUKUM: PROGRAM EVALUATION OF COGNITIVE THERAPY IN CHILDREN BEFORE LAW - Abdul Azis; Siti Zulaikha (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2022)
ABSTRACTIntroduction There are many reasons why a child is in conflict w'itñ th e law, including problems related to his mindset and self-concept so that the child takes deviant actions or the child has a low self-concept. BRSAMPK Handayani, East Jakarta, as tñ e Technical lmplementation Unit of the Indonesian Ministry ofsocial Affairs which serves social rehabilitation, including children in conflict with the law, provides psychosocial therapy, one of which is cognitive therapy. With cognitive therapy, children will be given understanding and education so the t they can change the mindset and perspective of children. The purpose of this study is to describe the evaluation of cognitive therapy for children facing the law at BRSAMPK Handayani. Methods This study uses a qualitative approach with o descriptive type of research. The data collection techniques used were observation, in-depth interviews, and documentation studies. Meanwhile, tñ e informants in this study were social workers and children in confiict with the law who became perpetrators and victims. Results The result of this study is that cognitive therapy conducted at BRSAMPK Handayani, East Jakarta has been well achieved in accordance with the objectives to be achieved. Likewise with the existence of professional staff and infrastructure that support the implementation of cognitive therapy. It can also be seen that there is a change in mindset or a change in negative though ts into positive ones, resulting in changes in children’s behavior. Kata Kunci : Cognitive therapy, Social Rehabilitation, BRSAMPK Handayani ABSTRAK Pendahuluan Banyak penyebab mengapa seorang anak berhadapan dengan hukum, salah satunya adalah masalah pola pikir dan konsep diri sehingga anak melakukan tindakan yang menyimpang ataupun anak memiliki konsep diri yang rendah. BRSAMPK Handayani Jakarta Timur sebagai unit pelaksana t eknis Kementerian Sosial Republik Indonesia yang melayani rehabilitasi sosial termasuk anak yang berhadapan dengan hukum memberikan terapi psikososial yang salah satunya adalah terapi kognitif. Dengan terapi kognitif anak akan diberikan pemahaman dan edukasi sehingga dapat merubah pola pikir dan cara pandang anak. Tujuan dari peneliuan ini adalah mendeskripsikan evaluasi terapi kognitif pada anak berhadapan hukum di BRSAMPK Handayani. Metode Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara mendalam, dan studi dokumentasi. Sedangkan informan dalam penelitian ini adalah pekerja sosial dan anak berhadapan hukum yang menjadi pelaku dan korban. Hasil penelitian ini adalah terapi kognitif yang dilakukan di BRSAMPK Handayani Jakarta Timur sudah tercapai dengan baik sesuai dengan tujuan yang ingin dicapai. Begitu juga dengan adanya staf yang profesional dan sarana prasarana yang menunjang pelaksanaan terapi Kata Kunci : Terapi Kognitif, Rehabilitasi Sosial, BRSAMPK Handayani